Short-Term Scheduling of Pump Station-integrated Cascade Hybrid Pumped Storage Systems - QIAN Jun; TAN Qiaofeng; WEN Xin; ZHENG Mingfen; SHEN Yanqing (工程科学与技术)
ObjectiveUnder the guidance of the dual carbon goals, the installation capacity of wind and solar energy in China has surged, and the issue of new energy consumption has become increasingly prominent. The addition of energy storage is an important measure to promote the absorption of new energy. This paper focuses on the pumped storage hydropower system formed by newly built storage pumping stations, proposing a dynamic control strategy for the reservoir capacity of multi-stage hybrid pumped storage power stations. A short-term scheduling study of the multi-stage hybrid pumped storage power station, based on the addition of pumping stations, is conducted. This method aims to achieve efficient operation of the energy storage pumping stations and provide a reference for the integration of new energy consumption and the construction of pumped storage.MethodsFirstly, a dynamic control strategy for the reservoir capacity of multi-stage hybrid pumped storage power stations was proposed. This strategy was designed to dynamically adjust the reservoir capacity based on the status of the reservoir and energy storage pumping stations, ensuring the efficient utilization of the energy storage pumping stations. Secondly, with the objective of minimizing the mean square deviation of the remaining load, a short-term scheduling model for multi-stage hybrid pumped storage stations, based on the addition of pumping stations, was developed. The traditional step-by-step optimization algorithm was improved to solve this model. Finally, a case study was conducted on the multi-stage hybrid pumped storage power station in the upper reaches of the Yellow River. The impact of the hybrid pumped storage station on peak shaving of the power grid and the absorption of new energy was analyzed. The effects of different installed capacities of pumping stations on the reservoir water level were explored, and the effectiveness of the proposed strategy was verified.Results and Discussions　This study analyzed the impact of cascade hybrid pumped storage (HPS) stations on peak regulation and renewable energy integration in the Qinghai Power Grid using 2021 dry-season data. Two configurations were compared: conventional cascade hydropower stations and cascade HPS stations.Under the conventional hydropower scheme, stations increased output during low-renewable periods to meet grid demand but reduced to forced output during midday renewable peaks, creating a residual load profile with dual peaks (morning/evening) and a midday valley, leading to 28.34% renewable curtailment. In the HPS scheme, hydropower stations also operated at forced output from 11 h to 18 h, while pump stations used curtailed renewable energy for water pumping. The stored water was later converted into electricity during peak hours, flattening the residual load profile, reducing renewable curtailment to 17.70%, and increasing hydropower generation from 260 million kWh to 293 million kWh. Over a typical dry-season week, the HPS scheme reduced residual load variance by 49.26%, while also decreasing the peak-valley difference and mean value.This studyConclusionsCompared to conventional cascade hydropower systems, cascade hybrid pumped storage systems were shown to demonstrate superior performance by reducing the mean squared error of residual load, increasing hydropower generation, and decreasing the curtailment rate of renewable energy. The rational configuration of pump station capacities was found to mitigate water level fluctuations in reservoirs equipped with energy storage pump stations at both upper and lower levels, although special attention was required for reservoirs with smaller regulation capacities and those at the terminal level. The dynamic reservoir capacity control strategy for multi-level hybrid pumped storage systems effectively extended the full-capacity pumping duration of pump stations, thereby maximizing the utilization of their pumping capabilities.